2015
DOI: 10.1073/pnas.1506645112
|View full text |Cite
|
Sign up to set email alerts
|

Knockout silkworms reveal a dispensable role for juvenile hormones in holometabolous life cycle

Abstract: Insect juvenile hormones (JHs) prevent precocious metamorphosis and allow larvae to undergo multiple rounds of status quo molts. However, the roles of JHs during the embryonic and very early larval stages have not been fully understood. We generated and characterized knockout silkworms (Bombyx mori) with null mutations in JH biosynthesis or JH receptor genes using genome-editing tools. We found that embryonic growth and morphogenesis are largely independent of JHs in Bombyx and that, even in the absence of JHs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(157 citation statements)
references
References 56 publications
10
147
0
Order By: Relevance
“…Moreover, null mutations of JH biosynthesis and JH receptor genes show precocious metamorphosis at the 3rd or 4th instar at the earliest. The authors suggest that the lack of competence for metamorphosis during the early larval instars may result from the absence of expression of the pupal specifier gene, Br (Daimon et al ., ; Daimon et al ., ). However, more recent experiments in B .…”
Section: The Status Quo Action Of Jh In Middle Juvenile Stagesmentioning
confidence: 97%
“…Moreover, null mutations of JH biosynthesis and JH receptor genes show precocious metamorphosis at the 3rd or 4th instar at the earliest. The authors suggest that the lack of competence for metamorphosis during the early larval instars may result from the absence of expression of the pupal specifier gene, Br (Daimon et al ., ; Daimon et al ., ). However, more recent experiments in B .…”
Section: The Status Quo Action Of Jh In Middle Juvenile Stagesmentioning
confidence: 97%
“…The goal is to develop N. denticulata into a tractable genetic model through transgenics and mutation screens. Methods used successfully in insects and amphipod crustaceans, such as CRISPR/Cas9, TALEN, and RNAi with tissue-specific expression constructs, may be applied to other crustaceans species (Gaj et al 2013; Daimon et al 2015; Enya et al 2015; Li et al 2015c; Martin et al 2016; Valzania et al 2016). Neocaridina denticulata has attributes that are essential for transgenic experiments: (1) they are freshwater animals that live in a wide range of temperatures and water chemistries; (2) relatively short intergenerational time (4–5 months); (3) small size for housing thousands of individuals in limited space; (4) fertilized eggs are relatively large and are brooded externally, facilitating the harvest of eggs for microinjection of gene constructs; (5) direct embryonic development; and (6) the cuticle is thin and transparent, which allows for observation of molt stages, gonad development, and tissue expression of reporter genes, such as red fluorescent protein, in live animals.…”
Section: Future Directions and Recommendationsmentioning
confidence: 99%
“…Daimon et al . () showed that embryonic growth and morphogenesis are largely independent of JHs, and precocious metamorphosis is induced at the earliest after the 2nd instar. They also suggested that an unidentified factor or signal is required to acquire the competence for metamorphosis.…”
Section: Genome Editing Accelerates Functional Dissection Of the B Mmentioning
confidence: 99%
“…However, this long-held paradigm was challenged when knockout B. mori with null mutations in JH biosynthesis or JH receptor genes were generated and characterized. Daimon et al (2015) showed that embryonic growth and morphogenesis are largely independent of JHs, and precocious metamorphosis is induced at the earliest after the 2nd instar. They also suggested that an unidentified factor or signal is required to acquire the competence for metamorphosis.…”
Section: Pathway Scale Gene Editingmentioning
confidence: 99%